The metaphore of the feast in Nietzsche - Buñuel Fanconi, Darío (Escritura e Imagen, 2019)
This article aims to offer a new reading of the metaphor “feast” in Nietzsche’s work that has traditionally been limited to an interpretation with an anthropological perspective. From Nietzsche’s treatment in some posthumous fragments of his last years, we propose to separate the idea of “feast” from the idea of community and offer it beyond the community since we understand that, for the nietzschean thought, any form of community is bound to the instinct of the herd.
Keywords: Nietzsche; feast; intoxication; art; community